2014
DOI: 10.1155/2014/656431
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Upper Airway Obstruction and Primary and Secondary Enuresis Nocturna in Children and the Effect of Surgical Treatment for the Resolution of Enuresis Nocturna

Abstract: Objective. The aim of this study is to investigate the coexistence of upper airway obstruction (UAO) and primary enuresis nocturna (PEN) and secondary enuresis nocturna (SEN) in children. Besides, the efficacy of surgery on resolution of enuresis nocturna is evaluated. Materials and Methods. The children with PEN and SEN were included in the first group and investigated for UAO in the Department of Otorhinolaryngology. During the same period, children who had been planned for an operation to treat UAO over 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…First, our study revealed that children in the comorbid group had a more severe form of adenoid hypertrophy compared to children with adenoid hypertrophy only, and a higher frequency of enuresis than in children with enuresis only. This is in agreement with reports by studies suggesting that enuresis is more prevalent in children with severe adenoid hypertrophy, and strongly associated with the severity of adenoid hypertrophy [6,29,30] , however, there are studies that do not confirm this relationship or do not report any relationship. [31] Heterogeneity in study settings and methodological differences of data sources, case definitions, and included age ranges may contribute to this great variability.…”
Section: Discussionsupporting
confidence: 91%
“…First, our study revealed that children in the comorbid group had a more severe form of adenoid hypertrophy compared to children with adenoid hypertrophy only, and a higher frequency of enuresis than in children with enuresis only. This is in agreement with reports by studies suggesting that enuresis is more prevalent in children with severe adenoid hypertrophy, and strongly associated with the severity of adenoid hypertrophy [6,29,30] , however, there are studies that do not confirm this relationship or do not report any relationship. [31] Heterogeneity in study settings and methodological differences of data sources, case definitions, and included age ranges may contribute to this great variability.…”
Section: Discussionsupporting
confidence: 91%